2019
DOI: 10.1111/jtxs.12468
|View full text |Cite
|
Sign up to set email alerts
|

Texture and color characteristics of swell‐dried ready‐to‐eat Zaghloul date snacks: Effect of operative parameters of instant controlled pressure drop process

Abstract: In this work, development of ready‐to‐eat snacks from Zaghloul date using swell‐drying process was studied. Pre‐dried Zaghloul date samples having 12% water content on dry basis were textured by instant controlled pressure drop technique (DIC) at different operative parameters, saturated steam pressure (p) and processing time (t), ranged from 0.2 to 0.6 MPa and from 9 to 35 s, respectively. The effect of these operative parameters on texture, color, and sensory characteristics of swell‐dried (SD) Zaghloul date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Swell-drying has also been applied to develop ready-to-eat snacks and expanded granule powders from Zaghloul dates (Phoenix dactylifera L.) [40]. Dates were pre-dried under CAD until a water content of 0.12 g H 2 O/g db was reached to be DIC textured at different operative parameters (200 to 600 kPa and from 9 to 35 s).…”
Section: Instant Controlled Pressure-drop Treatment On Fruitsmentioning
confidence: 99%
“…Swell-drying has also been applied to develop ready-to-eat snacks and expanded granule powders from Zaghloul dates (Phoenix dactylifera L.) [40]. Dates were pre-dried under CAD until a water content of 0.12 g H 2 O/g db was reached to be DIC textured at different operative parameters (200 to 600 kPa and from 9 to 35 s).…”
Section: Instant Controlled Pressure-drop Treatment On Fruitsmentioning
confidence: 99%
“…The mixture was homogenized in a blender and presented hot to the panelists including 70 members (25 males and 45 females aged 23-65 years) in coded samples. The panelists were provided with an instructed sheet and a glass of water as described by Mounir et al (2019a). The different samples were evaluated for the overall acceptability based on their 1/appearance, 2/color, 3/taste, and 4/odor using a nine-point hedonic scale (1 = extremely dislike to 9 = extremely like) according to Leite et al (2013).…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The color parameters; L*, a*, and b*, of different carob powders were evaluated according to Mounir et al (2019a) using a Hunter's Lab color analyzer (Color Flex EZ Spectrophometer, USA) which was standardized with a black and white tile before the measurement. Chroma (C*) and the total color change (DE) were respectively determined using Eqs.…”
Section: Color Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the pressure drops, several thermo-mechanical effects occur into the food material, such as expansion, instantaneous cooling of the products, and the rapid vaporization of volatile compounds [ 10 ]. Many fruit and vegetable materials have been subjected to this technology, such as strawberry [ 11 , 12 ], banana [ 13 ], pepper [ 14 , 15 ], garambullo [ 16 ], date [ 17 ] and chokecherry [ 18 ]; and research findings have shown that thanks to a porous structure newly generated by DIC, swell-drying reduced the drying time and preserved bioactive and nutritional food compounds.…”
Section: Introductionmentioning
confidence: 99%